Trade-off between inflation, interest and unemployment rate of Pakistan: A cointegration analysis - Yasar Mahmood; Rabia Bokhari; Muhammad Aslam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Pakistan is one of the developing countries in Asia. Destabilized economy is one of the major hurdles in the progress of Pakistan while inflation, interest and unemployment rates are three major indicators for destabilization. Purpose of the study is to investigate the link between these major economic variables that have great affect on the economic structure. Johansen's Cointegration test and Vector Error Correction Model (VECM) have been employed to find out the long run relationship between variables. Furthermore, Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) have been estimated. The results of the study indicate that inflation, interest and unemployment rates are cointegrated. It is found that interest and unemployment rates are both negatively related to the rate of inflation in the economy. But the rate of unemployment does not depend on inflation rate and interest rate.
Keywords: 330; Cointegration; Vector Error Correction Model (VECM); Impulse Response Function (IRF); Forecast Error Variance Decomposition (FEVD)